The 12CO/13CO ratio in turbulent molecular clouds - Szűcs, László; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2014)
The 13CO molecule is often used as a column density tracer in regions where the 12CO emission saturates. The 13CO column density is then related to that of 12CO by a uniform isotopic ratio. A similar approximation is frequently used when deriving 13CO emission maps from numerical simulations of molecular clouds. To test this assumption, we calculate the 12CO/13CO ratio self-consistently, taking the isotope-selective photodissociation and the chemical fractionation of CO into account. We model the coupled chemical, thermal and dynamical evolution and the emergent 13CO emission of isolated, starless molecular clouds in various environments. Selective photodissociation has a minimal effect on the ratio, while the chemical fractionation causes a factor of 2–3 decrease at intermediate cloud depths. The variation correlates with both the 12CO and the 13CO column densities. Neglecting the depth dependence results in ≤60 per cent error in 12CO column densities derived from 13CO. The same assumption causes ≤50 per cent disparity in the 13CO emission derived from simulated clouds. We show that the discrepancies can be corrected by a fitting formula. The formula is consistent with millimetre-wavelength isotopic ratio measurements of dense molecular clouds, but underestimates the ratios from the ultraviolet absorption of diffuse regions.
Gesehen am 10.03.2015
Im Titel sind die Zahlen 12 und 13 hochgestellt